Analytic philosophy : an anthology - Martinich, Aloysius; Sosa, David, 1966- (Chichester, West Sussex : Wiley-Blackwell, 2012)
"Featuring updates and the inclusion of nine new chapters, Analytic Philosophy: An Anthology, 2nd Edition offers a comprehensive and authoritative collection of the most influential readings in analytic philosophy written over the past hundred years. Features broad coverage of analytic philosophy, including such topics as ethics, methodology, and freedom and personal identity Focuses on classic or seminal articles that were especially influential or significant New articles in this edition include "Proof of an External World" by G. E. Moore, "Criteria, Defeasibility, and Knowledge" by John McDowell, "Sensations and Brain Processes" by J. J. C. Smart, selections from Sense and Sensibilia by J. L. Austin, "Other Bodies" by Tyler Burge, "Individualism and Supervenience" by Jerry Fodor, "Responsibility and Avoidability" by Roderick Chisholm, "Alternative Possibilities and Moral Responsibility" by Harry Frankfurt, and "Personal Identity" by Derek Parfit Offers diverse approaches to analytic philosophy by including readings from Austin, Wittgenstein, Quine, and Davidson "--
"Analytic Philosophy: An Anthology, 2nd Edition is a comprehensive and authoritative collection of the most influential readings in analytic philosophy written over the past hundred years. In addition to maintaining the first edition's coverage of seminal writings and the latest works on the philosophy of language, philosophy of mind, metaphysics, epistemology, ethics, and methodology, this second edition features nine additional chapters, including treatment of externalism in philosophy of mind by Burge and Fodor, and an important treatment of perception by McDowell. Other featured authors include Gottlob Frege, Bertrand Russell, W. V. Quine, David Lewis, Thomas Nagel, John Searle, Donald Davidson, Bernard Williams, and many more. With its breadth of scope and expert selection of the best classic and cutting edge writings, Analytic Philosophy: An Anthology, 2nd Edition represents an invaluable and essential resource for anyone interested in twentieth-century analytic philosophy"--
Machine generated contents note: Acknowledgments.Introduction.Part I :Philosophy of Language.1 "On Sense and Reference"(Gottlob Frege).2 "Thought"(Gottlob Frege.3 "On Denoting"(Bertrand Russell).4 "On Referring"(P. F. Strawson).5 "Meaning"(H. P. Grice).6 "Truth and Meaning"(Donald Davidson).7 "Identity and Necessity"(Saul Kripke).8 "Meaning and Reference"(Hilary Putnam).Further Reading in Philosophy of Language.Part II: Metaphysics.9 "On the Relations of Universals and Particulars"(Bertrand Russell).10 From the Tractatus Logico-Philosophicus(Ludwig Wittgenstein).11 "Particular and General"(P. F. Strawson).12 "On What There Is"(W. V. Quine).13 "The Identity of Indiscernibles"(Max Black).Further Reading in Metaphysics.Part III: Epistemology.14 "Proof of an External World"(E. Moore).15 From On Certainty:( Ludwig Wittgenstein).16 "Knowledge by Acquaintance and Knowledge by Description"(Bertrand Russell).17 "The Problem of the Criterion"(Roderick Chisholm).18 "Is Justified Knowledge True Belief?"(Edmund Gettier).19 "Studies in the Logic of Explanation"(Carl Hempel and Paul Oppenheim).20 "The New Riddle of Induction"(Nelson Goodman).21 "Epistemology Naturalized"(W. V. Quine).22 "Criteria, Defeasibility, and Knowledge"(John McDowell).Further Reading in Epistemology.Part IV: Philosophy of Mind.23 "Sensations and Brain Processes"(J. J. C. Smart).24 "The Nature of Mental States"(Hilary Putnam).25 Sense and Sensibilia(J. L. Austin).26 "Mental Events"(Donald Davidson).27 "What is it Like to Be a Bat?"(Thomas Nagel).28 "Mad Pain and Martian Pain"(David Lewis).29 "Can Computers Think?"(John Searle).30 "Other Bodies"(Tyler Burge).31 "Individualism and Supervenience"(Jerry Fodor).Further Reading in Philosophy of Mind.Part V: Freedom and Personal Identity.32 "The Conceivability of Mechanism"(Normal Malcolm).33 "Freedom and Resentment"(P. F. Strawson).34 "Human Freedom and Self"(Roderick Chisholm).35 "Alternative Possibilities and Moral Responsibility"(Harry Frankfurt).36 "The Self and the Future"(Bernard Williams).37 "Personal Identity"(Derek Parfit).38 "Action, Reasons, and Causes"(Donald Davidson).Further Reading in Freedom and Personal Identity.Part VI :Ethics.39 "The Subject Matter of Ethics"(G. E. Moore).40 "The Emotive Meaning of Ethical Terms"(Charles Stevenson).41 "Justice as Fairness"(John Rawls).42 "Modern Moral Philosophy"(G. E. M. Anscombe).43 "Morality as a System of Hypothetical Imperatives"(Philippa Foot).Further Reading in Ethics.Part VII: Methodology. 44 "The Elimination of Metaphysics"(A. J. Ayer).45 "Empiricism, Semantics, and Ontology"(Rudolf Carnap).46 "Two Dogmas of Empiricism"(W. V. Quine).47 "In Defense of a Dogma"(H. P. Grice and P. F. Strawson).48 "Philosophy and the Scientific Image of Man"(Wilfrid Sellars).49 The Blue and the Brown Books(Ludwig Wittgenstein).Further Reading in Methodology.Index.
Includes bibliographical references and index.
Keywords: Analysis (Philosophy)